Inhibition of Cell Proliferation and MAP Kinase and Akt Pathways in Oral Squamous Cell Carcinoma by Genistein and Biochanin A. Issue 3 (2010) - Johnson, Tara L.; Lai, Maria B.; Lai, James C. K.; Bhushan, Alok
Abstract : High morbidity and mortality associated with oral squamous cell carcinoma (OSCC) are largely attributable to late stage diagnosis. Despite significant advances in therapeutic strategies, the five-year survival rate for oral cancer remains at about 50%. A chemopreventive approach may be an effective alternative or adjunct to current therapies. Previous studies have shown anti-tumor effects of isoflavones in several cancers, including oral cancer. However, their mechanisms of action are still unclear. We hypothesized that isoflavones inhibit multiple signaling pathways implicated in oral carcinogenesis. To address our hypothesis, we investigated the effects of three isoflavone derivatives, genistein, biochanin A and daidzein, on SCC15 and SCC25 squamous cell carcinoma cell lines. In cell proliferation experiments, we found that genistein and biochanin A inhibited SCC15 and SCC25 cell growth with an IC50 of 50 μM. We also investigated the effect of isoflavones on ERK and Akt pathways. Our results, from western blot analysis, suggest that both genistein and biochanin A induced decreases in phosphorylation of ERK and Akt at treatment concentrations of 20, 50 and 100 μM. Taken together, our results clearly demonstrate a differential regulation of signaling pathways by various isoflavones in OSCC cell lines. Thus, tumor progression models can be utilized to study the preventive and therapeutic roles of isoflavones in oral cancer cell lines.